1989
DOI: 10.1210/endo-125-5-2745
|View full text |Cite
|
Sign up to set email alerts
|

The Presence and Estrogen Control of Immunoreactive Calbindin-D9kin the Fallopian Tube of the Rat*

Abstract: The present study was undertaken to localize and investigate the endocrine control of immunoreactive 9K calbindin-D9k in the fallopian tube (oviduct) of the rat. Rat fallopian tubes were excised with the uterus, immediately fixed by freeze-substitution, and processed for immunoperoxidase staining. Staining employed a rabbit antiserum against purified rat intestinal calbindin-D9k and the streptavidin-biotin technique. Calbindin-D9k immunoreactivity was localized to luminal epithelial cells of the fallopian tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…Previous reports indicate that E 2 is able to change the expression of different proteins in the rat oviduct (Mathieu et al 1989, Hermoso et al 1997, Pérez Martínez et al 2006; however, to our knowledge, no studies have been performed to determine whether these responses are different before and after mating. Here, we compared the effect of E 2 on gene expression in the oviduct of unmated and mated rats.…”
Section: Introductionmentioning
confidence: 85%
“…Previous reports indicate that E 2 is able to change the expression of different proteins in the rat oviduct (Mathieu et al 1989, Hermoso et al 1997, Pérez Martínez et al 2006; however, to our knowledge, no studies have been performed to determine whether these responses are different before and after mating. Here, we compared the effect of E 2 on gene expression in the oviduct of unmated and mated rats.…”
Section: Introductionmentioning
confidence: 85%
“…There is evidence that Ca 2ϩ -binding proteins are responsible for intracellular Ca 2ϩ storage and that the functions of (32). Experimental studies performed in vivo have shown that calbindin-D9K is localized in the ciliated epithelial cells (35) and that it is regulated by estrogen in rat fallopian tubes (7). In addition, the dependency of calbindin-D28K expression on estrogen has been reported in mouse fallopian tubes (19).…”
Section: Ajp-endocrinol Metabmentioning
confidence: 99%
“…This protein, first identified in rat intestine (Kallfelz et al 1967;Reiswig et al 1995), has two "EF" hands per monomer containing amino acid residues in a loop structure between a-helices functioning as the Ca 2+ binding site (Kligman and Hilt 1988). It has, so far, been detected in various other mammalian tissues including lung, kidney (Delorme et al 1983), growth cartilage (Balmain et al 1986), fallopian tube (Mathieu et al 1989), yolk sac (Delorme et al 1983;Bruns et al 1986), uterus (Delorme et al 1983;Warembourg et al 1987), and placenta (MacManus et al 1986;Müller et al 2000). The dynamic nature of the intrauterine expression of CaBP9k has been investigated in species such as rodents, ruminants, porcine species, and baboons.…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed that the placental expression of CaBP9k varies markedly between species. Indeed, in the rat reproductive system, CaBP9k has been localized to tissues such as the myometrium, the eudiometrical stroma of the non-pregnant uterus, the transporting epithelium of the visceral yolk sac, the intraplacental yolk sac IPYS (IPYS) (Delorme et al 1983;Bruns et al 1988), the luminal epithelium of the maternal uterus in late gestation, and the epithelial cell lining the fallopian tubes (Mathieu et al 1989). In mouse, CaBP9k was identified only in the endodermal cells of IPYS (Bruns et al 1985).…”
Section: Introductionmentioning
confidence: 99%